PERKEMBANGAN QIRĀ’ĀT DI INDONESIA: - Sa'adah, Faridatus (Lajnah Pentashihan Mushaf Al-Qur'an, 2019)
This research which uses a qualitative exploratory approach explores the Quranic memorizers (qurrÄ â€™) of seven techniques of reciting the holy Quran (qirÄ'Ät sabâ€˜ah) in Indonesia particularly those whose chains (sanad) are connected to KH.M. Moenawwir of Krapyak Yogyakarta. The data about the quranic memorizers (qurrÄ ') are obtained by using interview techniques and document study. Data collection was held by interviewing care takers, families, administrators and the alumni of the Pesantren Al-Munawwir Krapyak, that of Pesantren Holy Yanbu Holy Qur'an, that of Pesantren Ar-Roudlotul Mardliyyah Kudus, and that of Pesantren Manba'ul Huda Banyuwangi. This study found four layers of generation of teacher and student who successfully memorized and obtained the chains of seven techniques of reciting the holy quran (sanad qirÄâ€™Ät sabâ€˜ah) from the line of KH. M. Moenawwir. They studied the technique of reciting the holy quran (qirÄ'Ät) by using talaqqi method individually or better known as sorogan method. The information about the qurrÄâ€™ (Quranic memorizers using the method of seven techniques of reciting the holy quran (qirÄ'Ät sab'ah) can be utilized by the authorities and those are interested in developing science of reciting the holy quran (QirÄ'Ät) and the tradition of memorizing the quran using the method of seven techniques of reciting the holy quran (qirÄ'Ät sab'ah) such as the Ministry of Religious affairs, The institute of quranic studies and memorization (LPTQ), the group of Quranic reciters and memorizers ( Jam'iyyatul Qurra ' wal Huffadz ( JQH)) and other institutions such as pesantren and universities as well as individual who studies seven techniques of reciting the holy Quran (qiraat sabâ€™ah). Key words:memorization, memorizers, qirÄâ€™Ät sabâ€˜ah, (seven techniques of reciting the holy Quran),reciters having the chains (qurrÄâ€™ with sanad)